(untitled) (Scientia Agricola, 2015)
The geminivirus complex known as cassava mosaic disease (CMD) is one of the most devastating viruses for cassava (Manihot esculenta Crantz). The aim of this study was to use molecular-assisted selection (MAS) to identify CMD-resistant accessions and ascertain promising crosses with elite Brazilian varieties. One thousand two hundred twenty-four accessions were genotyped using five molecular markers (NS169, NS158, SSRY028, SSRY040 and RME1) that were associated with resistance to CMD, along with 402 SNPs (single-nucleotide polymorphism). The promising crosses were identified using a discriminant analysis of main component (DAPC), and the matrix of genomic relationship was estimated with SNP markers. The CMD1 gene, previously described in M. glaziovii, was not found in M. esculenta. In contrast, the CMD2 gene was found in 5, 4 and 5 % of cassava accessions, with flanking markers NS169+RME1, NS158+RME1 and SSRY28+RME1, respectively. Only seven accessions presented all markers linked to the CMD resistance. The DAPC of the seven accessions along with 17 elite cassava varieties led to the formation of three divergent clusters. Potential sources of resistance to CMD were divided into two groups, while the elite varieties were distributed into three groups. The low estimates of the genomic relationship (ranging from -0.167 to 0.681 with an average of 0.076) contributed to the success in identifying contrasting genotypes. The use of MAS in countries where CMD is a quarantine disease constitutes a successful strategy not only for identifying the resistant accessions but also for determining the promising crosses.